Emerging trends in education policy : unapologetic progressive conversations - Ransaw, Theodore S.; Boggs, Brian (Emerald Publishing Limited : Information Age Publishing, Inc., 2023)
"From the moment society first conceived an education system, there has been a need to have critical discussions about how best to provide education, and how best to create education policy. Because of the rapidly changing and fluid nature of technology, education has become the most crucial component to having a better life around the globe. The purpose of Emerging Trends in Education Policy: Unapologetic progressive conversations, is to highlight impactful policies, strategies initiatives, and approaches to educational reform globally, nationally, as well as locally through an edited volume. Emerging Trends in Education Policy offers readers the opportunity to read contributions to researchers and policymakers who like to make a ruckus to speak to an audience that appreciates disruption. Emerging Trends in Education Policy provides space for researchers to take intellectual risks and policymakers to be on the cutting edge of educational policy change. Educators often do not have the time to research and propose policy recommendations despite the fact they are the people that deliver the content. Professors often delay their more provocative findings and suggestions until after full tenure. By encouraging chapters from professors that were K-12 teachers at one time first, and researchers second, Emerging Trends in Education Policy: Unapologetic progressive conversation fulfills the need for innovative policy reform based on recommendations from practitioners with direct knowledge in the field"--